Influence of Geoelectric Field on Chemical Reactions on Earth - Shevchenko, Igor V. (Доповіді НАН України, 2016)
The existing understanding of chemical thermodynamics presupposes that at the same temperature
and other conditions being equal, the rate of a chemical reaction will always and
everywhere on Earth be constant. We have found that geoelectric field generated by the Earth’s
ionosphere, is capable of exerting a strong influence on the rate of chemical processes. Because
of the revolution of the Earth around the Sun and varying intensity of the solar irradiance
the geoelectric field is highly dynamic and causes the rate of some chemical reactions on
the Earth to vary over wide ranges within a year. Існуюче уявлення про хімічну термодинаміку передбачає, що при однаковій температурі
та інших рівних умовах швидкість хімічної реакції завжди і повсюди на Землі буде
однаковою. Автором встановлено, що геоелектричне поле, що генерується іоносферою
Землі, спроможне сильно впливати на швидкість хімічних процесів. Внаслідок обертання
Землі навколо Сонця та інтенсивності сонячного випромінювання, що змінюється,
геоелектричне поле дуже динамічне та спроможне викликати зміну швидкості деяких
хімічних реакцій в широких межах впродовж року. Существующее представление о химической термодинамике предполагает, что при
одинаковой температуре и прочих равных условиях скорость химической реакции всегда и везде на Земле является постоянной. Автором обнаружено, что геоэлектрическое поле, генерируемое ионосферой Земли, способно оказывать сильное влияние на скорость химических процессов. Вследствие вращения Земли вокруг Солнца и изменяющейся
интенсивности солнечного излучения геоэлектрическое поле чрезвычайно динамично и способно вызывать изменение скорости некоторых химических реакций на Земле в больших пределах в течение года.